Co-design of agroecological transition pathways: Outcomes of an early Pause and Reflect of the CGIAR Initiative on Agroecology - Staiger Rivas, Simone; Quintero, Marcela; Wiederkehr Guerra, Gabriela Patricia; Orjuela, Guillermo; González, Carolina; Dickens, Chris (CGIAR System Organization, 2022)
While CGIAR has several past and ongoing research experiences on agroecology it is the first time that such an ambitious initiative is being supported, in a way that integrates capacities across the CGIAR and with partners. This is one of the reasons why the Initiative leadership invited project members for an early Pause & Reflect workshop that was held in Kenya in October 2022, only six months after the official kick-off. The event united the leaders and co-leaders of the five work packages and the coordinators of all seven countries as well as partner representatives from Burkina Faso, Kenya, and Zimbabwe to share first experiences and assure effective interaction among countries and work packages.